2003
DOI: 10.1046/j.1442-200x.2003.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and management of intra‐abdominal infections in children

Abstract: The present review describes the microbiology, diagnosis, and management of intra-abdominal infections in children. Infection generally occurs due to the entry of enteric micro-organisms into the peritoneal cavity through a defect in the wall of the intestine or other viscus as a result of obstruction, infarction, or direct trauma. Mixed aerobic and anaerobic flora can be recovered from the peritoneal cavity of these patients. The predominant aerobic isolates are Escherichia coli, and enterococci; the main ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…As in adults, Bacteroides isolates are most predominant in infections that have an intra-abdominal origin; normally present in the GI tract, these organisms may enter the peritoneal cavity due to a disturbance such as perforation, obstruction, or direct trauma. A few studies evaluating the microbiology of the peritoneal cavity and postoperative wounds in children following perforated appendix in pediatric patients found that Bacteroides species were recovered from 93% of peritoneal fluids, along with enteric gram-negative bacteria and enterococci (38). Complications following peritonitis may include subphrenic, hepatic, splenic, and retroperitoneal abscesses (39) (which may occur secondary to appendicitis), necrotizing enterocolitis, pelvic inflammatory disease, tubo-ovarian infection, surgery, or trauma (39).…”
Section: Anaerobes In Pediatric Infectionsmentioning
confidence: 99%
“…As in adults, Bacteroides isolates are most predominant in infections that have an intra-abdominal origin; normally present in the GI tract, these organisms may enter the peritoneal cavity due to a disturbance such as perforation, obstruction, or direct trauma. A few studies evaluating the microbiology of the peritoneal cavity and postoperative wounds in children following perforated appendix in pediatric patients found that Bacteroides species were recovered from 93% of peritoneal fluids, along with enteric gram-negative bacteria and enterococci (38). Complications following peritonitis may include subphrenic, hepatic, splenic, and retroperitoneal abscesses (39) (which may occur secondary to appendicitis), necrotizing enterocolitis, pelvic inflammatory disease, tubo-ovarian infection, surgery, or trauma (39).…”
Section: Anaerobes In Pediatric Infectionsmentioning
confidence: 99%
“…For example, Haemophilus influenza and Neisseria meningitidis are commensal bacteria of the upper respiratory tract that can cause life-threatening diseases once they invade their host (11)(12)(13)(14)(15)(16). Upon host entry, H. influenza and N. meningitidis replicate in the blood stream, resulting in a steadily increasing bacteremia within hours after infection (12,(17)(18)(19).…”
mentioning
confidence: 99%
“…Similar Þ ndings were corroborated by previous studies. [15,16] Although the reports of ileal perforations are many, studies showing aetiological diagnosis conÞ rmed by culture of blood sample or lymph node aspirate or ulcer edge or peritoneal ß uid are scarce. [15] The APACHE II score is of value in predicting outcome and in stratiÞ cation of patients with intra-abdominal infection as it is independently associated with the rate of mortality.…”
Section: Discussionmentioning
confidence: 99%